Become the CEO of You, Inc. : a pioneering executive shares her secrets for career success - Butler, Susan Bulkeley (Book collections on Project MUSE., 2012)
How do you turn your dreams into reality? How do you make things happen for you, rather than let things happen to you? Don?t be humble about who you are and what you are capable of. Stand tall and stand out. Be known. Be recognized as a leader, and most of all, know you are a leader,? is Susan Bulkeley Butler?s call to action for her readers to take responsibility for their lives. In this updated second edition of the best-selling Become the CEO of You, Inc., Susan has provided strategies for improving your life and new techniques for advancing your career. The book is focused around her?Make it Happen? model, which is based on three decades of experience working with Fortune 500 companies. The steps include: Develop a clear aspiration for You, Inc.; build your board of directors; develop your plan to make your aspiration happen; and navigate your day-to-day journey. The second edition is completely revised and includes new topics such as: The importance of executive coaching; developing your image in today?s world; taking a long-term view of your life and career; new opportunities for balancing career and family; use of social networking techniques? the good, bad and ugly; and preparing for promotion.